2024
DOI: 10.1021/acsaenm.3c00622
|View full text |Cite
|
Sign up to set email alerts
|

Engineering of an Isoreticular Series of CALF-20 Metal–Organic Frameworks for CO2 Capture

Karuppasamy Gopalsamy,
Dong Fan,
Supriyo Naskar
et al.

Abstract: A series of linker-substituted ultramicroporous CALF-20 metal−organic frameworks (MOFs) were built in silico, and their CO 2 capture performances over N 2 in flue gas conditions were systematically computationally explored. Among the various linker substitutions explored, squarate-linker-incorporated CALF-20 (SquCALF-20) was demonstrated to show a larger CO 2 uptake at 0.15 bar (3.6 mmol/g) and higher CO 2 /N 2 selectivity (500) in dry conditions compared to pristine CALF-20. Interestingly, this MOF was shown … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…Various materials can be employed for CO 2 adsorption, categorized based on the interaction between CO 2 and the sorbent: physisorbents and chemisorbents. , Physisorbents like metal–organic frameworks (MOFs), ,, activated carbons, or zeolites , are noted for poor performance, exhibiting low CO 2 capacity at low concentrations and lacking selectivity. In contrast, chemisorbents prove highly effective at ultralow CO 2 concentrations, making them preferable for DAC at levels like 420 ppm in the air. ,, Among chemisorbents, amine-functionalized sorbents stand out due to their high CO 2 uptake, selectivity, adaptability to various conditions, and low energy requirements. , In these materials, CO 2 reacts with amines, forming chemical bonds that facilitate substantial uptake, even at low CO 2 concentrations through Reactions –, depending on moisture availability. ,, Solid amine-based sorbents are categorized by their preparation methods and the bonds formed between amines and the support material, as illustrated in Figure , .…”
Section: Introductionmentioning
confidence: 99%
“…Various materials can be employed for CO 2 adsorption, categorized based on the interaction between CO 2 and the sorbent: physisorbents and chemisorbents. , Physisorbents like metal–organic frameworks (MOFs), ,, activated carbons, or zeolites , are noted for poor performance, exhibiting low CO 2 capacity at low concentrations and lacking selectivity. In contrast, chemisorbents prove highly effective at ultralow CO 2 concentrations, making them preferable for DAC at levels like 420 ppm in the air. ,, Among chemisorbents, amine-functionalized sorbents stand out due to their high CO 2 uptake, selectivity, adaptability to various conditions, and low energy requirements. , In these materials, CO 2 reacts with amines, forming chemical bonds that facilitate substantial uptake, even at low CO 2 concentrations through Reactions –, depending on moisture availability. ,, Solid amine-based sorbents are categorized by their preparation methods and the bonds formed between amines and the support material, as illustrated in Figure , .…”
Section: Introductionmentioning
confidence: 99%
“…1a ). Other CALF-20 derivatives, as well as their composites, have been equally explored 14 19 . However, to date, the mechanical/thermal behaviours of CALF-20 have been overlooked both experimentally and theoretically.…”
Section: Introductionmentioning
confidence: 99%
“…However, to date, the mechanical/thermal behaviours of CALF-20 have been overlooked both experimentally and theoretically. Although several studies have been reported on the competitive adsorption of CO 2 and H 2 O in CALF-20 and derivatives 19 – 21 the lack of understanding on the pressure/thermal-induced structure evolution of CALF-20 is critical in the context of using this MOF under diverse working conditions. The determination of MOF mechanical/thermal properties generally requires the deployment of sophisticated experimental techniques as well as the consideration of high-quality samples making the whole testing process far from trivial 22 , 23 .…”
Section: Introductionmentioning
confidence: 99%